Analysis of Physical Characteristics of Airports that Affect Airline Operational Efficiency - Jeeradist, Thongchai (Suan Dusit Graduate School Academic Journal, 2023)
The objectives of the research were 1) to study the physical characteristics of airports that affected the operational efficiency of airlines 2) to find guidelines to increase the operational efficiency of airlines in accordance with the physical characteristics of the airports. The qualitative research with in-depth interviews was implemented with 3 types of key informants, namely 4 individuals of airport operations, 4 individuals of airline operations, 4 individuals of air traffic control, totaling 12 individuals. The non-participant observation of airline operations at the airport apron and passenger terminal was conducted together with the analysis of documents from the International Civil Aviation Organization (ICAO), the International Air Transport Association (IATA), the Civil Aviation Authority of Thailand (CAAT) and related researches. The triangulation method was employed to analyze data from in-depth interviews. The results showed that 1) the airport’s potential was linked to the airport’s physical characteristics, including airside and landside. 2) the physical characteristics of airports affected the operational efficiency of airlines as follows: (1) Flight punctuality efficiency (2) Airport Slot Time allocation and airline flight schedule (3) Air density of air traffic due to physical characteristics of airports (4) Efficiency and readiness of passenger terminal facilities (5) Availability of ground service equipment in the apron (6) Environmental impacts around the airport and nearby areas. The research also found that flight delay caused by inclement weather and technical effects of aircraft affected airlines’ operational efficiency.